Pédagogie de l'enseignement supérieur en France : état de la question - Nicole Poteaux (Centre National d'Enseignement à Distance, 2013)
Judging by the numerous reports penned by institutional experts all over France on restructuring the university system, galvanising research, and boosting student success - not to mention guiding teacher-researchers as their profession develops - it may be useful to reflect on what is at stake in this fervent discussion. Why should teacher-researchers now receive pedagogical training? Why should we create teaching services, teaching support centres, and institutes for teacher-researcher teaching innovation and professional development? This article aims to clarify the diverse trends that are stirring up universities, as much in terms of the words they use and their meaning as of the perspectives that are taking shape in the field of teaching for the future of French higher education. Following a brief history of the use of the word, we will consider the stakes present within the university context, challenges that we will bring face to face with the established existence of didactics and education sciences without forgetting digital development. Finally, we will outline perspectives for potential research in this field, which is both young in name and old in the practices of teacher-researchers.